Synthesis and study of structural properties of MoS2@MoO3 hybrid structure for highly enhanced H2S gas response - Azhar Mohammed Abd; Mohammed Ajmi Abd (Peerian Journals Publishing, 2025)
In this work, we synthesized MoS2@MoO3 hybrid structure by a two-step method. In the first step, the thin films of MoS2 was obtained by chemical bath deposition (CBD) method. During the synthesis, the  interaction was between ammonium molybdate ( ) and sodium sulfide( ) solution, a products contain a mixture between amorphous molybdenum disulfides and oxide is obtained.
Keywords: chemical bath deposition; dramatizing; gas sensor; Hydrogen sulfide